Bifunctional nanocapsules for magnetic resonance imaging and photodynamic therapy. Issue 106 (2nd November 2016) - Zhang, Hecheng; Peng, Shan; Xu, Suying; Chen, Zhengguang
Abstract : A bifunctional protein nanospheres was successfully constructed through self-assembly of hydrolysed α-lactalbumin for magnetic resonance imaging and photodynamic therapy. Abstract : Here we present the fabrication of bifunctional nanocapsules via cation (Ca 2+ /Gd 3+ ) induced self-assembly of partially hydrolysed α-lactalbumin. The prepared nanospheres, encapsulated with photosensitizer (Rose Bengal) and Gd 3+ ion, show great potentials for magnetic resonance imaging and photodynamic therapy with a target-specific manner.